Impact of socio-demographics on Malocclusion and Traumatic dental injuries among 13-15 years old children in province II of Nepal - Gupta, Rahul; Mahanta, Swagat; Sah, Rishi Pratap (Orthodontic Journal of Nepal, 2019)
Introduction: Malocclusion may not be pathological condition, but it negatively affects the quality of life. The purpose of the study was to assess the role of socio-demographics on malocclusion and traumatic dental injuries among adolescents. Materials & Method: A cross-sectional descriptive study was conducted with a sample of 320 students from government and private schools. Student’s in the age range from 13-15 years were included. A structured questionnaire was used to assess demographic characteristics, socio-economic status, frequency of dental visit and tooth brushing, self-perceived need for orthodontic treatment. Index of orthodontic treatment need (IOTN) and Traumatic Dental Injury (TDI) were recorded. Result: The study showed that self-reported orthodontic treatment need was greater among Private school students as compared to Government. IOTN-DHC more severe Grade 4, Grade 3 type of treatment needs were greater among government students. While Grade 1 & Grade 2 type of treatment needs was found to be greater among private students. Grade 5 & Grade 4 type of orthodontic treatment needs was greater among government students, 83(51.9%) & 48 (30%) as compared to private students, 21(13.1%) & 25(15.6%). While Grade 1, Grade 2 & Grade 3 type of orthodontic treatment needs was lesser among government students, 6(3.8%), 8(5.0%) & 15(9.4%) as compared to private students, 42(26.2%), 49(30.6%) & 23(14.4%) respectively. Complicated type of dental injury was greater among government students. Conclusion: The study indicates the presence of socio demographic gradient in orthodontic treatment need and Traumatic dental injuries.